Silk Protein Gene Engineering and Its Applications: Recent Advances in Biomedicine Driven by Molecular Biotechnology - Ji X; Li Y; Wang J; Wang G; Ma B; Shi J; Cui C; Wang R (Drug Design, Development and Therapy)
Xingxiang Ji,1,* Yanyan Li,2,* Jingsheng Wang,3,* Gang Wang,3,* Bin Ma,4 Jingfei Shi,5 Chao Cui,6,7 Ruiming Wang1 1State Key Laboratory of Biobased Material and Green Papermaking, Qilu University of Technology, Shandong Academy of Sciences, Jinan, Shandong, 250353, People’s Republic of China; 2Key Laboratory of Maternal & Fetal Medicine of National Health Commission of China, Shandong Provincial Maternal and Child Health Care Hospital Affiliated to Qingdao University, Jinan, 250014, People’s Republic of China; 3Department of Cardiovascular Medicine, The Second Affiliated Hospital of Shandong First Medical University, Taian, Shandong, 271000, People’s Republic of China; 4Department of Cardiovascular Medicine, Taian City Taishan District People’s Hospital, Taian, Shandong, 271000, People’s Republic of China; 5Department of Clinical and Basic Medicine, Shandong First Medical University, Jinan, Shandong, 250000, People’s Republic of China; 6Scientific Research Department, Qilu Hospital of Shandong University Dezhou Hospital, Dezhou, Shandong, 253000, People’s Republic of China; 7Department of Pharmacy, The Affiliated Taian City Central Hospital of Qingdao University, Taian, Shandong, 271000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chao Cui, Scientific Research Department, Qilu Hospital of Shandong University Dezhou Hospital, Dezhou, Shandong, 253000, People’s Republic of China, Email hbkjcuichao@126.com Ruiming Wang, State Key Laboratory of Biobased Material and Green Papermaking, Qilu University of Technology, Shandong Academy of Sciences, Jinan, Shandong, 250353, People’s Republic of China, Email ruiming3k@163.comAbstract: Silk protein, as a natural polymer material with unique structures and properties, exhibits tremendous potential in the biomedical field. Given the limited production and restricted properties of natural silk proteins, molecular biotechnology has been extensively applied in silk protein genetic engineering to produce novel silk proteins with specific properties. This review outlines the roles of major model organisms, such as silkworms and spiders, in silk protein production, and provides a detailed introduction to the applications of gene editing technologies (eg, CRISPR-Cas9), transgenic expression technologies, and synthetic biology techniques in silk protein genetic engineering. By analyzing the genetic factors influencing silk protein expression, this review further elaborates on the innovative applications of silk proteins in drug delivery systems, tissue engineering and regenerative medicine (eg, skin, bone, cartilage, and vascular repair), as well as antibacterial immune strategies. Notably, modified silk proteins expressed by transgenic silkworms demonstrate significant advantages in enhancing drug bioavailability and promoting cell proliferation and differentiation. In conclusion, silk protein gene engineering, through continuous innovations in molecular biotechnology, has provided an effective pathway for the production of high-performance silk protein materials. The extensive applications of these modified silk proteins in the biomedical field have not only expanded the functionality of silk proteins but also offered new approaches to address medical challenges. In the future, the development of silk protein gene engineering will further rely on interdisciplinary integration to promote in-depth research and the expansion of industrial applications of silk proteins.Keywords: silk protein, genetic engineering, molecular biotechnology, performance optimization, biomedical applications, tissue engineering, regenerative medicine